Di Carta e d'Altro : Libri d'artista. (Prato : Centro per l'Arte Contemporanea Luigi Pecci, 1994)
Andre, Carl ; Arienti, Stefano ; Baj, Enrico ; Bagnoli, Marco ; Bartolini, Luciano ; Barzagli, Massimo ; Berriolo, Elena ; Bobo, Antonio ; Brecht, George ; Canevari, Paolo ; Caruso, Luciano ; Castellani, Enrico ; Catelani, Antonio ; Canevago, Umberto ; Conte, Bruno ; Corsini, Vittorio ; Cucchi, Enzo ; Dubuffet, Jean ; Fontana, Lucio ; Fisher, Joel ; etc.
Di Carta e d'Altro : Libri d'artista, Centro per l'Arte Contemporanea Luigi Pecci, Prato - CID/Arti Visive, Prato, 3 - 30 giugno 1994
boek